Indonesia’s Public Diplomacy to Improve its Image in Japan: through the Indonesia-Japan Friendship Day in 2022-2023 - Pratama, Iqbal Rizki Anugrah; Hidayatullah, Nur Luthfi (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2024)
This study aims to describe Indonesia's public diplomacy to improve its image in Japan through the Indonesia Japan Friendship Day (IJFD) in 2022- 2023. The authors argue that Indonesia held IJFD as a public diplomacy strategy in response to its positive image decline in Japan during the Covid-19 pandemic. The researchers used a descriptive qualitative approach. Secondary data was obtained from literature studies, including official documents of the Indonesian Embassy in Tokyo as well as books, journal articles, and news sites. The results of this study show that Indonesia's public diplomacy strategy to improve its image in Japan through the IJFD in 2022-2023 was carried out through three dimensions. First, news management, which was carried out using digital media by domestic and foreign actors. Second, strategic communication, which was carried out through the establishment of a special